A Model of Consumer Purchase Decisions Based on Product Quality and Sales Promotion Aspects for Ikawangi Egg Noodles In Karawang - Ulum, Miftahul; Savitri, Citra; Fadilla , Syifa Pramudita (Jurnal Indonesia Sosial Sains, 2026)
The purpose of this study is to examine how sales promotion and product quality affect consumers' decision to buy Ikawangi MSME egg noodles in Karawang Regency. A total of 96 people participated in this descriptive quantitative study, including Ikawangi Egg Noodle traders and regular consumers. Multiple linear regression was used to assess data collected from a closed-ended questionnaire on a five-point Likert scale. The findings show that purchasing decisions are positively and significantly influenced by sales promotions and product quality. While sales promotion is important for attracting attention and creating purchase intent, product quality is a key element that influences a customer's purchase decision. Purchasing decisions are most influenced by product quality, with sales promotion coming in second. This shows that attractive advertising strategies and high-quality products can increase consumer attention and purchase choices. This research provides an empirical contribution for local MSMEs, especially Ikawangi, in strengthening competitiveness through improving product quality and implementing more innovative and sustainable promotional strategies.